PENGARUH PENGGUNAAN KOMIK EDUKATIF TERHADAP MINAT MEMBACA BAHASA INDONESIA SISWA KELAS IV UPT SDN 142 TAMBOKE - Aulya, Zilfa; Madeamin, Rosmini; Syakur, Abdan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the use of educational comics on the interest in reading Indonesian in fourth-grade students at UPT SDN 142 Tamboke. This study used a quantitative approach with an experimental research type, specifically a pre-experimental One Group Pretest–Posttest Design. The study population was all 25 fourth-grade students at UPT SDN 142 Tamboke, who were also sampled using a saturated sampling technique. Data collection techniques were conducted through questionnaires, observations, tests, and documentation. The results showed that the average score of students' reading interest increased from 65 in the pretest to 91 in the posttest. Furthermore, students' reading comprehension also increased from an average of 71 in the pretest to 90 in the posttest. The results of the hypothesis test using a paired sample t-test showed a significance value of 0.000 (<0.05), thus H₀ was rejected and H₁ was accepted. Based on these results, it can be concluded that the use of educational comics has a significant and positive effect on increasing reading interest and Indonesian language comprehension among fourth-grade students at UPT SDN 142 Tamboke.